Bone response to functionally loaded, two‐piece zirconia implants: A preclinical histometric study. Issue 3 (30th December 2017) - Janner, Simone F. M.; Gahlert, Michael; Bosshardt, Dieter D.; Roehling, Stefan; Milz, Stefan; Higginbottom, Frank; Buser, Daniel; Cochran, David L.
Abstract: Objective: To evaluate the bone response to a two‐piece zirconia implant in comparison with a control titanium implant in the canine mandible 4 and 16 weeks after restoration. Material and Methods: Zirconia and titanium implants were alternately placed bilaterally in healed mandibular molar and premolar sites of five canines. Full‐ceramic single‐tooth restorations were cemented after 6 weeks of transmucosal healing, allowing for full functional loading of the implants. Histologic and histometric analyses were performed on orofacial and mesiodistal undecalcified sections of the specimens obtained upon sacrifice after 4 and 16 weeks of functional loading. Bone‐to‐implant contact (BIC), multinucleated giant cells‐to‐implant contact (MIC), crestal bone level, and peri‐implant bone density were histometrically assessed. Results: All 60 implants and 60 restorations were still in function after 4 and 16 weeks of loading in both test and control groups. No implant loss, no implant or abutment fracture, and no chipping of the restorations could be detected. Histometric analysis showed no statistically significant differences between zirconia and titanium implants in BIC, crestal bone level, and peri‐implant bone density at both time points. Between 4 and 16 weeks, the crestal bone level around zirconia implants showed a small but statistically significant increase in its distance from the implant shoulder. MIC was very low on both implant types and both time points and decreased statistically significantly overtime. Conclusion: The present two‐piece zirconia implant showed a similar bone integration compared to the titanium implant with similar surface morphology after 4 and 16 weeks of loading.